2012
DOI: 10.1128/aem.05114-11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Feed Efficiency and Diet on Adaptive Variations in the Bacterial Community in the Rumen Fluid of Cattle

Abstract: Limited knowledge of the structure and activities of the ruminal bacterial community prevents the understanding of the effect of population dynamics on functional bacterial groups and on host productivity. This study aimed to identify particular bacteria associated with host feed efficiency in steers with differing diets and residual feed intake (RFI) using culture-independent methods: PCR-denaturing gradient gel electrophoresis (DGGE) and quantitative real-time PCR analysis. PCR-DGGE profiles were generated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
126
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 54 publications
10
126
0
5
Order By: Relevance
“…Low-RFI animals (Nkrumah et al 2006;Hegarty et al 2007). Comparisons of ruminal microbiomes between low-and high-RFI animals using a variety of methods have shown differences in bacterial and archaeal community profiles correlated with RFI, although these associations are often influenced by the energy content of the diet (Guan et al 2008;Zhou et al 2010;Carberry et al 2012;Hernandez-Sanabria et al 2012). Methanogen-related differences observed in these studies included a specific high-RFI-related PCR-DGGE band associated with Methanobrevibacter smithii PS (Zhou et al 2010), an elevated abundance of Methanosphaera stadtmanae, and Methanobrevibacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Low-RFI animals (Nkrumah et al 2006;Hegarty et al 2007). Comparisons of ruminal microbiomes between low-and high-RFI animals using a variety of methods have shown differences in bacterial and archaeal community profiles correlated with RFI, although these associations are often influenced by the energy content of the diet (Guan et al 2008;Zhou et al 2010;Carberry et al 2012;Hernandez-Sanabria et al 2012). Methanogen-related differences observed in these studies included a specific high-RFI-related PCR-DGGE band associated with Methanobrevibacter smithii PS (Zhou et al 2010), an elevated abundance of Methanosphaera stadtmanae, and Methanobrevibacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…2012; Hernandez‐Sanabria et al . 2012; Golder et al . 2014), but the relationship between the ruminal pH, VFA and microbiota composition in SARA cattle is unclear.…”
Section: Pathophysiological Evaluation Of Sara By Continuous Monitorimentioning
confidence: 99%
“…They also observed that bacterial profiles were more likely clustered within a certain breed, suggesting that host genetics may play a role in rumen microbial structure. Subsequently, Hernandez-Sanabria et al (2012) examined whether specific bacterial groups were associated with cattle feed efficiency, and whether these relationships are affected by the host diet. Steers belonging to the same RFI group under both low-energy and high-energy diets were used to identify specific bacterial phylotypes related to feedefficiency traits.…”
mentioning
confidence: 99%